Space,Time and Memory in the Hippocampal Formation 2014
DOI: 10.1007/978-3-7091-1292-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Nonspatial Representations in the Lateral Entorhinal Cortex

Abstract: The hippocampus is thought to function as a "cognitive map," which stores nonspatial information such as items and events in a spatial framework. In order to understand the computations involved in creating such conjunctive nonspatial + spatial representations, it is essential to understand the function of hippocampal inputs. Medial entorhinal cortex (MEC) is known to convey spatial information to the hippocampus. In this chapter, we discuss recent evidence showing that lateral entorhinal cortex (LEC) conveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 100 publications
(122 reference statements)
2
1
0
Order By: Relevance
“…Convergence of scene and object information is compatible with recent rodent work that shows joint coding of scene and object information (notably operationalized as spatial and non-spatial information, respectively) along CA1 and within the lateral EC ( Deshmukh, 2014 ; Doan et al, 2019 ; Vandrey et al, 2021 ; Wilson et al, 2013 ; Yeung et al, 2019 ). Note that a supplemental analysis of information processing in the cortical source regions showed indeed, specific object processing in perirhinal source regions (see appendix 5).…”
Section: Discussionsupporting
confidence: 85%
“…Convergence of scene and object information is compatible with recent rodent work that shows joint coding of scene and object information (notably operationalized as spatial and non-spatial information, respectively) along CA1 and within the lateral EC ( Deshmukh, 2014 ; Doan et al, 2019 ; Vandrey et al, 2021 ; Wilson et al, 2013 ; Yeung et al, 2019 ). Note that a supplemental analysis of information processing in the cortical source regions showed indeed, specific object processing in perirhinal source regions (see appendix 5).…”
Section: Discussionsupporting
confidence: 85%
“…Convergence of item and contextual information is compatible with recent rodent work that shows joined coding of spatial (location) and non-spatial (object) information along CA1 and within the lateral EC (Deshmukh, 2014;Doan et al, 2019;Vandrey et al, 2021;Wilson et al, 2013;Yeung et al, 2019). However, we cannot confirm reports about higher functional activity for object than scene processing within these areas in the human brain Navarro Schröder et al, 2015;Berron et al, 2018;also indicated in Dalton et al, 2018 andSchultz et al, 2012).…”
Section: Portions -Subiculum/ca1 Border Routesupporting
confidence: 82%
“…Furthermore, we show that integration of feature and spatial coding occurs within mEC and that mEC cells can serve as a source for the emergence of feature coding by the hippocampus, in addition to direct inputs from lEC (Deshmukh, 2014; Knierim et al, 2006; Renno-Costa et al, 2010). LEC lesions were found to produce a 30 % impairment in hippocampal rate coding (Lu et al, 2013), which indicates that remaining entorhinal inputs may provide a major contribution to rate coding.…”
Section: Discussionmentioning
confidence: 85%